2018
DOI: 10.1016/j.artd.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility and content of individualized adult reconstructive hip and knee/musculoskeletal oncology fellowship web sites

Abstract: BackgroundAccessible, adequate online information is important to fellowship applicants. Program web sites can affect which programs applicants apply to, subsequently altering interview costs incurred by both parties and ultimately impacting rank lists. Web site analyses have been performed for all orthopaedic subspecialties other than those involved in the combined adult reconstruction and musculoskeletal (MSK) oncology fellowship match.MethodsA complete list of active programs was obtained from the official … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…In this study, 83% of foot and ankle websites had either direct links or links requiring multiple steps to access the program. This is in contrast to shoulder and elbow (61%), pediatrics (74%), 2 spine (71%), 18 adult reconstruction (77%), 5 orthopedic sports medicine (93%), 14,21 hand (86%), 8 musculoskeletal oncology (82%), 22 and trauma (94%). 16 The 2017 study of orthopedic sports medicine fellowship accessibility by Yayac et al found that 47% of programs listed on the AOSSM had a functional link to the program’s personal website, 21 compared to 18% with shoulder and elbow programs through ASES, 24 whereas 37% of hand surgery fellowships had a functional link from the ASSH directory.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 83% of foot and ankle websites had either direct links or links requiring multiple steps to access the program. This is in contrast to shoulder and elbow (61%), pediatrics (74%), 2 spine (71%), 18 adult reconstruction (77%), 5 orthopedic sports medicine (93%), 14,21 hand (86%), 8 musculoskeletal oncology (82%), 22 and trauma (94%). 16 The 2017 study of orthopedic sports medicine fellowship accessibility by Yayac et al found that 47% of programs listed on the AOSSM had a functional link to the program’s personal website, 21 compared to 18% with shoulder and elbow programs through ASES, 24 whereas 37% of hand surgery fellowships had a functional link from the ASSH directory.…”
Section: Discussionmentioning
confidence: 99%
“…Although a specific fellowship-associated professional society is a logical starting point for potential applicants, Google search is a search engine commonly used to find program websites. Shoulder and elbow fellowships had similar percentages of programs with either direct links or links requiring multiple steps to access the program (76%) when compared with orthopedic foot and ankle fellowships (72%), 4 pediatrics (74%), 1 spine (71%), 10 and adult reconstruction (77%) 3 but still lagged behind the percentages for orthopedic sports medicine (93%), 8 , 12 hand (96%), 11 musculoskeletal oncology (82%), 13 and trauma (94%). 9 …”
Section: Discussionmentioning
confidence: 99%
“…The accessibility of orthopedic fellowship websites has been studied for orthopedic surgery subspecialties including sports medicine, 8 , 12 adult reconstruction, 3 foot and ankle, 4 hand, 5 , 11 trauma, 9 spine, 10 pediatrics, 1 musculoskeletal oncology, 13 and shoulder and elbow. 14 When looking at the accessibility and content related to shoulder and elbow fellowship websites specifically, the results were poor, with only 64% of programs having individual websites.…”
mentioning
confidence: 99%
“…Recent research [6] , [7] concludes that we should do a better job making such information available to our residents. In addition to logistical, academic, and research opportunity information highlighted by Young et al.…”
mentioning
confidence: 99%
“…In addition to logistical, academic, and research opportunity information highlighted by Young et al. in this edition of Arthroplasty Today [6] , we also need to share intangible aspects of our profession that may be helpful in decision-making about job choices. As we better understand how to communicate career advice to our trainees and they ask if they will fit into our world, what better litmus test than to ask them when they feel they are in the zone .…”
mentioning
confidence: 99%